THE URBAN ENVIRONMENTAL ENGINEERING CONDITION OF UDUPI TALUK: A GIS EVALUATION URBAN AMENITIES WITH A FOCAL POINT PREDICTION OF POTENTIAL IMPROVEMENT OF URBANIZATION - Udayashankara, H N; Maddodi, B.S.; Raghavan, B.R.; V.T, Shema (European Scientific Journal, ESJ, 2013)
Urban Environmental Engineering is the application of science and engineering techniques to improve the natural environment to provide healthy water, air, and land for human habitation including infrastructure. The focal point is on the sustainable development of an urban entity where development of industrial and natural resources elevates and sustains energy needs of a civic population. This dissertation is aimed at developing a centralized system to carry out the analysis of urbanization of the Udupi Taluk with inputs from various interdisciplinary fields of demography, commerce, education, industries, health and tourism. To brawl with the problems of environmental degradation and to meet the challenges of sustainable development, it is suggested that the use of remote sensing and GIS in conjunction with geospatial data is of vital importance. There is need for the use of an urban information database that can be formulated using remote sensing data and GIS techniques. This is possible as GIS technology is unique in embracing spatial data of various parameters that could be modeled to bring out a multi-parametric relation in nature. The end result would provide spatial variations in the form of digital maps. These maps and their polygons would be imported in a GIS environment and the results would be used in query-models and thereby establishing the urban development of Manipal and the Udupi taluk. The output would shift the interpretations from single parametric to multi-parametric relation and this would enable the end users such as governmental agencies to pool data and adopt new strategies in dealing with urbanization in a comprehensive manner.